Electronic Service Quality and Participant’s Trust in Encouraging PT. Astra Life Insurance Purchase Decisions in DKI Jakarta - Irma Situmorang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Business competition in the era of globalization is very competitive, both in domestic and international markets. Basically, every human being in his life will face risks. Quality of Electronic Services is a “potential strategic weapon to beat competitors. The increasingly critical customer situation in terms of quality forces the company to "maintain and improve the quality of its Electronic Services so that there is no dissatisfaction from the company's customers in order to compete with other similar companies. This type of research is using a quantitative approach, as the research methodology. This study aims to carry out the phenomenon through data collection to examine a particular population or sample, by taking random samples, collecting data using quantitative or statistical data analysis with the aim of testing hypotheses. it is known that the largest percentage of respondents' responses are in the answer choices disagree. This means that respondents assess that their preference is to choose PT. Astra Life not because of the location of the PT. Astra Life which is easy to reach, but looking at other things including product quality even though location is a supporting factor. User trust plays a very important role in determining purchasing decisions. PT. Astra Life is able to make users quite believe in its existence and its products. The clarity of information provided by the claims administration officer of PT. Astra Life makes users believe that the claim submission is being processed properly, so users are willing to wait until the process is complete and then choose PT. Astra Life is back as insurance. So, Trust has an influence on the purchasing decisions of participants in choosing health insurance products PT. AstraLife.